ANALYSIS OF THE IMPLEMENTATION OF OCCUPATIONAL HEALTH AND SAFETY IN SCIENCE LABORATORIES: LITERATURE REVIEW - Kevin Aditia; Endah Febri Setiya Rini; Bramastia Bramastia (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2026)
Occupational safety and health are an important part of supporting a smooth and safe science learning process. A laboratory with good occupational safety and health standards is able to support the effectiveness of learning while preventing dangerous accidents for students. The aim of this research is to analyze the implementation of occupational safety and health in Indonesian science laboratories. This type of research is a literature study. Examples of articles used are sourced from Google Scholar with the time period 2014-2023. The data analysis technique used is the synthetic matrix method. The research results show that the application of occupational safety and health in science laboratories is quite diverse. There are still many obstacles in science laboratories in implementing occupational safety and health according to standards which are influenced by human factors (knowledge) and infrastructure supporting occupational safety and health. The conclusion from this research is that there are obstacles to implementing occupational safety and health in science laboratories which are influenced by human factors and supporting infrastructure.